1954
DOI: 10.1161/01.res.2.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The Zero of Potential of the Electric Field Produced by the Heart Beat: The Problem with Reference to Homogeneous Volume Conductors

Abstract: The acceptable zeros of the potential of the electrical fields produced by certain dipole distributions in homogeneous volume conductors is discussed. A bridge circuit is described by which a solution of the three-arm and the four-arm central terminals of Wilson may be solved for a zero of potential of the field produced by an arbitrary distribution of dipoles in a homogeneous volume conductor. An acceptable zero of potential for evaluation of the potentials in a locus on the "body" surface distant from the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1954
1954
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…We also report the polarity of the WCT based upon the orientation of the QRS feature present in the signal. Similarly to previous studies [3,4], we noted that with "N" signals, polarity is not clearly positive or negative i.e., the positive deflection amplitude almost matches the negative deflection at the QRS feature. Reported amplitude measurements are averaged across at least five consecutive beats.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…We also report the polarity of the WCT based upon the orientation of the QRS feature present in the signal. Similarly to previous studies [3,4], we noted that with "N" signals, polarity is not clearly positive or negative i.e., the positive deflection amplitude almost matches the negative deflection at the QRS feature. Reported amplitude measurements are averaged across at least five consecutive beats.…”
Section: Methodssupporting
confidence: 88%
“…Empirical confirmation of Frank's hypotheses about the amplitude and variability of the WCT came almost simultaneously when measurements of WCT (requiring the human body to be encased in a metal structure totally submerged in water for the duration of the recording), showed that Wilson's central point is non-stationary during the cardiac cycle and has a large amplitude (up to 40% of Einthoven's ECG signal amplitudes). Details of these results were published by both H.C. Burger and R. Bayley et al [3,4]. However, until now, without a valid alternative, this largely simplified hypothesis still lies at the base of modern clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Confirmation of errors and variability of the WCT during the cardiac cycle have been measured employing an “integrator electrode.” This procedure requires the entire human body to be encased in a metal structure and then immersed in water (neutral reference) during the measurement of ECG. Unfortunately, due to the cumbersomeness of the measurement process, this technique was used only for few experimental trials [ 15 , 16 ]. In recent years, the significance of the WCT and even its physical location has also been debated [ 9 , 10 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The theory of a zero of potential on the Wilson central terminal depends in part upon the requirement that every electrode which makes a contribution to the terminal has a potential function which is that of an unweighted resultant of the cardiac dipole distribution. 1 This function is in effect that of a point dipole or doublet. 6 The objection concerning the lack of remoteness of electrodes is synonymous with that in which the cardiac distribution of dipoles requires a weighted resultant for the potential function.…”
Section: Discussionmentioning
confidence: 99%
“…N a previous report it was shown that = l id 4vR\ V JJ V. dsi = 0 (1) Wherein V p is the arbitrary-dipole function for the sphere; Si is the spherical surface of a large integrating electrode (fig. 1); and V p , the average value of V p , is independent of the position of the dipole distribution within Si and is zero.…”
mentioning
confidence: 99%